Harun Ar-Rasyid: Perkembangan ilmu pengetahuan pada masa Islam klasik (786–809 M) - Nuzulul Hidayati; Marsudi Marsudi (Universitas Negeri Malang, 2021)
Most of us are very familiar with how the development of science in Europe, from the Dark Age to the Industrial Revolution, to forget how the development of science in the Islamic world. If Europe experienced a Dark Age, at that time, Islamic science was in its heyday. The triumphs did not escape the leaders at that time. In this article, the author will only focus on how the development of science during Harun ar-Rashid's time, including: 1) what is the background of Harun Ar-Rasyid, 2) what was the policy of Harun ar-Rashid's time, 3) how the science that developed in the era of Harun Ar-Rasyid. Sebagian besar dari kita sangat mengenal bagaimana perkembangan Ilmu pengetahuan di Eropa, dari masa Dark Age sampai Revolusi Industri hingga melupakan bagaimana perkembangan ilmu pengetahuan di dunia Islam. Jika Eropa mengalami masa Dark Age, pada masa itulah, Ilmu pengetahuan Islam sedang pada masa Kejayaannya. Kejayaan-kejayaan itu tidak luput dari para pemimpin pada masa itu. dalam artikel ini, penulis hanya akan memfokuskan bagaimana perkembangan ilmu pengetahuan pada masa Harun Ar-Rasyid, diantaranya: 1) bagaimana latar belakang Harun Ar-Rasyid, 2) bagaimana kebijakan pada masa Harun Ar-Rasyid, 3) bagaimana ilmu pengetahuan yang berkembang pada masa Harun Ar-Rasyid.